Da interação virtual à influência social : um estudo com seguidoras de uma influenciadora digital - Santos, Karen Batista (2020)
Digital influencers are individuals who have the ability to influence consumption and lifestyle decisions of those who are part of their social network. Seeking to investigate how this influence occurs in the online environment of social media, this research aimed to analyze the process of social influence, from the virtual social interaction between digital influencers and their followers. To this end, we adopted, in this study, theories widespread in the field of sociology and social psychology, such as symbolic interactionism and social influence, as theoretical support to carry out the analysis of a psychosocial behavior, using an interpretive approach. From the exploratory observation carried out in profiles of digital influencers, it was possible to combine theory with practice, creating a theoretical framework, which was used to analyze how social influence occurs on Instagram. Thus, a netnography on Instagram was made, with participant observation in the profile of the digital influencer of fashion and beauty Rica de Marré and her followers. Open interviews were also conducted with followers of the influencer. In addition, documents were analyzed, such as blog posts on the influencer's blog and articles on websites about her. Data analysis was done through narrative analysis. The analyzed categories that followed the proposed framework were: discourse of the digital influencer; virtual interaction with the digital influencer; feeling of intimacy with the digital influencer; feeling of belonging to the group; identification with the digital influencer; digital influencer as a reference; reproduction of the speech / behavior of the digital influencer; and reconstructing the follower's self. The main results showed that the constant interaction with the digital influencer causes a feeling of intimacy in the followers, and that the influencer becomes a reference for the followers, thus exercising an influence on their behavior. This influence happens both in terms of consumption and in other behaviors, such as the reproduction of slang and jargon that the influencer uses in her speech. The interviewed followers stated that they did not feel they belong to a group, which was observed only when there is a face-to-face interaction, as in ―encounters‖ with the influencer. Some of the interviewees also indicated in their statements that there was a reconstruction of the self, which demonstrates that the social influence that happens on social media goes beyond the influence on consumption.